Analysis of Students' Critical Thinking Ability Instruments in Thermodynamics Material Phase F SMA/MA Reviewed from Validity, Reliability, Level of Difficulty and Differentiation - Batubara, Nurjannah; Emiliannur, Emiliannur (Department of Physics Universitas Negeri Padang, 2025)
This study aims to determine the quality of critical thinking ability test instruments on the material Phase F Thermodynamics of SMA/MA in terms of validity, reliability, level of difficulty, and differentiating power. The research method used is a descriptive technique. The data consists of 31 sheets of student answers in grade XI of the 2025/2026 school year. The data were analyzed using several formulas of validity, reliability, difficulty, and differentiation. The method used to collect data is the test method. The results showed that 20 questions were valid and 1 question was invalid. The level of reliability is good where the value of the reliability coefficient r_11> is 0.842 so that the question instrument is declared reliable. Meanwhile, the difficulty level of the 21 questions was stated to be moderate, the difficulty index was in the range of 0.30 < kindergarten ≤ 0.70. The difference in the good category is 2 questions, in the enough category there are about 12 questions, which is said to be bad there are about 7 questions.